2012
DOI: 10.1002/jclp.20868
|View full text |Cite
|
Sign up to set email alerts
|

Public Speaking in Social Phobia: A Pilot Study of Self‐Ratings and Observers' Ratings of Social Skills

Abstract: The results are inconsistent with the cognitive model, because patients with SAD did not underestimate their performance. Compared with spontaneous interactions, the clear rules established for such social situations as speeches may result in less cognitive distortion for SAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…It is important to note that not all previous studies are consistent with an effect of social anxiety confined only to overt signs of anxiety. Some studies have found poorer observer ratings of fluency and voice intonation during a speech [15] and vocal clarity and eye contact during a conversation task [16] for patients with SAD compared to controls. However, a tabulated summary of past research findings [10] seems to suggest that where the ‘performance’ aspects of social behavior are also affected, this generally appears to be in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that not all previous studies are consistent with an effect of social anxiety confined only to overt signs of anxiety. Some studies have found poorer observer ratings of fluency and voice intonation during a speech [15] and vocal clarity and eye contact during a conversation task [16] for patients with SAD compared to controls. However, a tabulated summary of past research findings [10] seems to suggest that where the ‘performance’ aspects of social behavior are also affected, this generally appears to be in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of other studies have identified a link between social anxiety and impaired social behavior. Levitan et al [15] found that patients with SAD were rated significantly more poorly on observer ratings of voice intonation and fluency during a three-minute speech compared to controls. Other studies have also found patients with SAD to be rated more poorly by observers on adequacy of eye contact and speech clarity [16] and as exhibiting more “negative social behaviors” (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…De modo geral, os estudos encontrados na literatura sobre os fatores relacionados ao falar em público, como já citado anteriormente, estão voltados mais para populações com transtorno de ansiedade social (Harb, Eng, Zairder, & Heimberg, 2003;Laukka et al, 2008), com altos níveis de ansiedade social (Kim, Lundh, & Harvey, 2002;Schultz, Alpers, & Hofmann, 2008) e, também, para comparações entre grupos com e sem o transtorno mencionado (Angélico, Crippa, & Loureiro, 2012;Levitan et al, 2012;Rapee & Abbott, 2007;Voncken & Bögels, 2008) e com diferentes níveis de ansiedade social (Cody & Teachman, 2011;Thompson & Rapee, 2002;Wenzel & Holt, 2003). Em contrapartida, a amostra deste estudo foi composta apenas por universitários que não foram submetidos à avaliação clínica, segundo critérios diagnósticos, para transtornos psiquiátricos ou quaisquer condições subclínicas, impossibilitando, assim, que seus dados fossem comparados com aqueles obtidos nas demais pesquisas da área.…”
Section: Discussionunclassified
“…In Levitan, Falcone, Placido, Krieger, Pinheiro, et al, (2012) 18 socially phobic and 18 normal participants were compared in terms of a three-minute speechgiving. Five elements of social skills as well as the overall performance were rated.…”
Section: Are the Socially Phobic Different From Normal Individuals Inmentioning
confidence: 99%